THE IMPACT OF EDUCATION TECHNOLOGY IN TEACHING AND LEARNING - Balalle, Himendra; Weerasinghe, Tudor (European Journal of Research and Reflection in Educational Sciences, 2021)
The extraordinary progress and technological growth in the world are witnessed. In recent years, technology has also emerged through laptops, smartphones, mobile phone software, websites, text messages and social networking platforms. This advancement indicates that technology in various environments, like the education sector, has benefited greatly. We can see the value of education technologies with different apps for distance education, the internet, teachers and students themselves. This article aim is to provide a summary of the significance and use of education technology in the classroom.
Keywords: Educational technology, Technology and learning, PESCEP Factors , Teaching strategies, Learner–Centered Education.